Pengaruh Penambahan SiO2 dan TiO2 terhadap Sifat Hidrofobik Komposit Kitosan- ZnO Pada Kain - Dina Kartika Maharani; Nur Lailiyah (Unesa Journal of Chemistry, 2022)
This study purposed to determine the effect of adding TiO2 sol and SiO2 sol to chitosan-ZnO composites on the hydrophobic properties of fabrics through the fabric coating process. The data obtained of consisted qualitative and quantitative data. Data analysis used qualitative descriptive manner. The addition of TiO2 and SiO2 to Chitosan-ZnO using the sol-gel method. Composite coating on the fabric using the dip-coating method with a volume ratio of TiO2:ZnO 1:1 and SiO2:ZnO 1:1. Hydrophobicity test using the WCA method obtained contact angle of the chitosan-ZnO is 101o, chitosan-TiO2/ZnO is 142o and chitosan-SiO2/ZnO is 127o, then characterized using FTIR, showed the interaction of chitosan and ZnO marked by a peak in the area of ​​430 cm-1; 1556 cm-1; 1397 cm-1; 1338 cm-1; 3242 cm-1; 1052 cm-1 and 1019 cm-1. The formation of Chitosan-ZnO/TiO2 was seen from the wave shift and changes in the absorption intensity of Chitosan-ZnO at peak of 3242 cm-1 to 3450 cm-1; 1556 cm-1 to 1548 cm-1; 1397 and 1338 cm- 1 became 1400 and 1336 cm-1; 1052 and 1019 cm-1 became 1151 and 1023 cm-1 and a new peak appeared at 850 cm-1. The formation of Chitosan-ZnO/SiO2 was seen from the wave shift and changes in the absorption intensity of Chitosan-ZnO at peak of 3242 cm-1 to 3257 cm-1; 1556 cm-1 to 1589.34 cm-1; 1397 and 1338 cm-1 becomes 1401 and 1342 cm-1; 1052 and 1019 cm-1 becomes 1066 and 1020 cm-1 also new peaks of 938 cm-1. Keywords: Chitosan-ZnO Composite, TiO2, SiO2, Hydrophobic